FIGO good practice recommendations on the use of pessary for reducing the frequency and improving outcomes of preterm birth. Issue 1 (14th September 2021) - Grobman, William A.; Norman, Jane; Jacobsson, Bo; ,
Abstract: A pessary is a device made of synthetic material that is placed in the vagina and has been used for prevention of preterm birth. It has been suggested that a potential mechanism of the pessary is alteration of the cervico‐uterine angle to a more posterior position, which reduces cervical compression in women with a singleton pregnancy and a short cervical length. Pessaries should not be used in routine clinical care to reduce the frequency of preterm birth or to improve outcomes (e.g. neonatal outcomes) related to preterm birth. In women with a twin pregnancy—regardless of cervical length—pessaries should not be used in routine clinical care to reduce the frequency of preterm birth or to improve outcomes (e.g. neonatal outcomes) related to preterm birth. Presently there is no sufficient evidence suggesting that pessaries should be used as a standard treatment to prevent preterm birth; their use should be reserved for study populations. Synopsis: Pessary for prevention of preterm delivery is presently not recommended and should only be used for study populations.